Auto-Bäcklund Transformation, Similarity Reductions and Solitons of an Extended (2+1)-Dimensional Coupled Burgers System in Fluid Mechanics - Gao, Xin-Yi; Guo, Yong-Jiang; Shan, Wen-Rui (Qualitative theory of dynamical systems, 2022)
Burgers-type equations are seen in cosmology, hydrodynamics, plasma physics, hurricane dynamics, statistical dynamics, traffic modelling, etc. For an extended ( 2 + 1 )-dimensional coupled Burgers system in fluid mechanics, concerning the velocity components in the fluid-related problems, our symbolic computation brings forth an auto-Bäcklund transformation with some solitons, and two sets of the similarity reductions. Our results rely on the coefficients in the system.